Agripina é Roma-Manhattan e outras experiências héliocinematográficas - Sheery, Yardena do Baixo [UNESP] (2015)
This work is an attempt to approach, by several different ways; to Agripina is Rome-Manhattan, shortcut super-8 movie made by Hélio Oiticica in 1972, along his stay in New York City. Consequently, this work also takes a closer look to other cinematographic productions in the rich and unique Oiticica's universe.